2021
DOI: 10.1021/acsapm.1c00444
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Polymer Particles Containing Quaternary Ammonium for Antimicrobial Particulate Surfactants and Defoaming

Abstract: The preparation of multifunctional polymer particles containing quaternary ammonium molecules by emulsion iodine transfer polymerization (emulsion ITP) via polymerization-induced self-assembly was proposed for the first time. Poly(2methacryloyloxy ethyl trimethyl ammonium chloride-dimethylamino ethyl methacrylate 12 alkyl chain length)-iodide (P(MTMA-QAC 12 ) 12 -I) was first synthesized by solution iodine transfer polymerization. It was simultaneously used as a macro-chain transfer agent and emulsifier in emu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Reproduced with permission. [ 99 ] Copyright 2021, American Chemical Society. B) The W/O/W Pickering double emulsion.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 99 ] Copyright 2021, American Chemical Society. B) The W/O/W Pickering double emulsion.…”
Section: Applicationsmentioning
confidence: 99%
“…Kanmlangmak et al reported a Pickering emulsion system stabilized by polymer nanoparticles with antimicrobial and defoaming properties. [99] The functional particulate emulsifier containing quaternary ammonium (QA) is prepared based on emulsion iodine transfer polymerization (emulsion ITP). With a water contact angle of ≈90°, the oil droplets were stabilized without coalescence over a year.…”
Section: Microbe Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Among them, the compounds of QASs are the most widely used because of immediate efficacy as the positively charged QASs groups are easy to adsorb into the surface of the negatively charged bacterial cells, destroy the cell plasma membrane, and make the cell membrane unable to withstand osmotic pressure and exudates. 7,8 Copolymers containing QASs have attracted a great deal of attention due to its long-acting antibacterial, 9 low toxicity 10 and an ability to self-assemble into a variety of precisely controlled periodic nanostructures. 11,12 Researchers have developed some methods for preparing polymer particles, such as emulsion polymerization, seed swelling polymerization, block copolymer self-assembly, self-assembly solvent evaporation method, 13,14 and interfacial polymerization.…”
Section: Introductionmentioning
confidence: 99%
“… 14,21 However, only one study by Kamlangmak et al introduced a successful investigation of copolymer nanoparticles containing DMAEMA by emulsion iodine transfer polymerization via polymerization-induced self-assembly for inhibition of growth of E. Coli and S. aureus combining the effect of positively charged particles and the presence of an alkyl chain. 22 …”
Section: Introductionmentioning
confidence: 99%